Enriching Culinary Variety through Ice Cream Innovation with Traditional Herbal Medicine Turmeric Acid at Jinggo Café & Restaurant - Dwi Nur Hidayati, Shinta; Randhi Nanang Darmawan; Wiralatief Sanjaya, Aditya (Journal of Language, Communication, and Tourism, 2024)
The development of Tourism encourages the development of health tourism  (wellness  tourism  and  herbal  tourism)  by re-socializing herbal medicine, by innovating the utilization of  sour  turmeric  herbal  medicine  into  sour  turmeric  herbal ice  cream  so  that  it  becomes  a  culinary  alternative.  This study  aims  to  determine  the  manufacturing  process,  the level  of  public  liking  and  cost  analysis.  The type of approach used  is  research  and  development  (R&D)  with the 4D development model (Define, Design, Development and  Dissemination)  which  uses  hedonic  and  hedonic quality organoleptic tests. The results showed that the best recipe used a ratio of 40% herbal medicine: 100% milk with a favorability level of 86.7%. In the process of making sour turmeric  herbal  ice  cream  through several  stages,  namely preparation  of  ingredients,  mixing  ingredients, pasteurization,  homogenization,  aging  or  freezing, packaging  and  storage.  With the selling price of the Sour Turmeric Herb Ice Cream product IDR 6,000 / portion.